The Woman's Heart: Insights into New Potential Targeted Therapy - Gianfrilli, Daniele; Pofi, Ricardo; Feola, Tiziana; Lenzi, Andrea; Giannetta, Elisa (Current Medicinal Chemistry, 2017)
Cardiovascular disease is an increasingly common cause of death in women. There is as yet no consensus on the analysis of cardiovascular risk factors with regard to the specific, personalised treatment of pre- and post-menopausal women. Clinically significant cardioprotective and antiremodelling effects have been observed in animal and human studies exploring chronic inhibition of phosphodiesterase type 5 (PDE5). The relationship between the heart, estrogens and PDE5 inhibitors (PDE5is) remains unclear. Experimental data suggest potential beneficial effects on cardiac geometry, function, endothelial function and microvascular coronary flow in women. It was recently postulated that the efficacy of PDE5is is estrogen-dependent in female heart disease. A registered randomised, placebo-controlled study, RECOGITO (NCT01803828), aimed at identifying the genderspecific efficacy of long-term PDE5 inhibition in diabetic cardiomyopathy, is currently recruiting patients. Estrogen receptor modulation could be a new promising approach to heart protection via PDE5is. PDE5is could be indicated as a gender-oriented strategy in modulated cardiac dysfunction and remodelling and in cardiac risk factors for selected cardiovascular diseases.
Keywords: NO